2020
DOI: 10.1177/0963689720962052
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF-related Protein 9 Inhibits High Glucose–Induced Oxidative Stress and Apoptosis in Retinal Pigment Epithelial Cells Through the Activation of AMPK/Nrf2 Signaling Pathway

Abstract: Diabetic retinopathy (DR) is one of the common complications of diabetes mellitus. C1q/TNF-related protein 9 (CTRP9) has been demonstrated to be associated with the progression of diabetes and relative complications. However, its role in DR and underlying action of mechanism are not yet well understood. In the present study, human retinal pigment epithelial ARPE-19 cells were cultured under high concentration of glucose to simulate hyperglycemia condition in vitro. Our results showed that the expression of CTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…AMPK, a serine/threonine kinase sensitive to cellular energy alterations and processes linking energetics to longevity, acts as a major downstream component of CTRP9 signaling. CTRP9 overexpression has been reported to protect against HGinduced endothelial oxidative damage and apoptosis by phosphorylating AMPK (Cheng et al, 2016;Cheng et al, 2020). Treatment with recombinant CTRP9 protein significantly increased the phosphorylation of AMPK and inhibited cytokine-induced vascular inflammation and leukocyte adhesiveness in human aortic endothelial cells (Jung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, a serine/threonine kinase sensitive to cellular energy alterations and processes linking energetics to longevity, acts as a major downstream component of CTRP9 signaling. CTRP9 overexpression has been reported to protect against HGinduced endothelial oxidative damage and apoptosis by phosphorylating AMPK (Cheng et al, 2016;Cheng et al, 2020). Treatment with recombinant CTRP9 protein significantly increased the phosphorylation of AMPK and inhibited cytokine-induced vascular inflammation and leukocyte adhesiveness in human aortic endothelial cells (Jung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AGEs can destroy the biological function of mitochondria [19] and inhibit normal autophagy in cells [20], which provides an important platform for researchers to study the molecular mechanisms and drug interventions associated with mitochondrial and autophagy-related central nervous system diseases. Some studies reported that AMPK showed protective effects on different cell lines, such as podocytes [21], hippocampal neurons [22], retinal pigment epithelium ARPE-19 cells [23], and Müller cells [24]. According to some reports, AMPK directly promotes autophagy by phosphorylating autophagy-related proteins in the mTORC1, ULK1, and PIK3C3/VPS34 complex or indirectly promotes autophagy by regulating the expression of autophagy-related genes that ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of CTRPs has been reported in the drusen of human donor eyes with AMD [52]. Additionally, the CTRP family has reported to mediate glucoseinduced oxidative stress and apoptosis in RPE cells [53]. Ifi204 (interferon gamma inducible protein) is a cytosolic DNA sensor involved in initiation of a type 1 interferon response and activation of the inflammasome pathway in response to bacterial or viral infection [54,55].…”
Section: High-fat Diet May Affect Expression Of Genes Involved In Inflammatory Pathways In Germ-free Micementioning
confidence: 99%